Incidence and spontaneous clearance of gonorrhea and chlamydia infections among men who have sex with men: a prospective cohort study in Zhuhai, China - Lyu, Hang; Tang, Haotong; Feng, Yunlong; Hu, Shuyan; Wang, Yuyu; Zhou, Lanlan; Huang, Shanzi; Li, Jiarun; Zhu, Huamei; He, Xi; Tang, Weiming; Zhou, Yi; et al. (Frontiers in Public Health, 2024)
Background: Men who have sex with men (MSM) face significant risks of Chlamydia trachomatis (CT) and/or Neisseria gonorrhoeae (NG) infection. Nevertheless, only limited studies have looked into the site-specific infection and clearance of CT/NG. In order to prevent transmission, it is essential to understand the underlying factors that drive infection and spontaneous clearance. Methods: A 12-week cohort study examined the association between CT/NG infection, selfclearance, and sexual behaviors among MSM. The Willingness Service recruited participants who completed weekly questionnaires and provided urine, throat, and rectal swab samples. Results: The study involved 151 men, in which 51 (33.8%) were diagnosed with CT/NG infection during the study period. HIV (OR=11.31), kissing (OR=1.59), receptive oral sex (OR=36.64), and insertive anal sex (OR=19.73) constituted significant risk factors. 100% condom use (OR=5.78) and antibiotic (OR=7.53) were more likely to cause spontaneous clearance. Discussion: MSM may engage in riskier sexual behaviors due to insufficient knowledge and awareness of STI prevention, leading to increased susceptibility to NG/CT. It is crucial to concentrate on enhancing health education for MSM. Conclusions:This study found that the rectum was the most prevalent site of CT/NG and sexual behavior can influence the infection. Additionally, the appropriate use of antibiotics and consistent condom use may contribute to clear spontaneously.